2022
DOI: 10.1002/ccr3.5209
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic lymphohistiocytosis/macrophage activation syndrome (HLH/MAS) following treatment with tisagenlecleucel

Abstract: Chimeric antigen receptor (CAR) T cell–related HLH/MAS is an unusual manifestation of severe cytokine release syndrome (CRS) with poor prognosis and a challenging diagnosis. The establishment of specific diagnosis criteria is essential, and the combination of several techniques for CAR T‐cell follow‐up, allows a more precise management of this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Few cases of post-anti-CD19 CAR T-cell therapy for HLH/MAS have been reported so far, and the best treatment for such a complication has not been established [15]. Here, the ultimate use of EP after failure of tocilizumab and siltuximab resulted in a dramatic and unexpected clinical recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few cases of post-anti-CD19 CAR T-cell therapy for HLH/MAS have been reported so far, and the best treatment for such a complication has not been established [15]. Here, the ultimate use of EP after failure of tocilizumab and siltuximab resulted in a dramatic and unexpected clinical recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the cases of 2 patients with suspected HLH/MAS following treatment with tisagenlecleucel have been reported, one treated with cyclophosphamide and extracorporeal cytokine adsorption and the other one with dexamethasone, EP, and anakinra, a recombinant IL-1 receptor antagonist. Both these patients however soon died in progression, even if the second one showed some HLH/MAS improvement [18]. Another case of response to anakinra has been reported [19].…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggested that anakinra might serve as a steroid-sparing agent and usually was the last medication to be weaned without impacting CAR T-cell efficacy [12,14]. Given the proposed clinical benefits of using anakinra, the prospective trials for preemptive use of anakinra for patients who are at high risk of developing severe CRS and/or carHLH are urgently needed.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…Симпто мы могут варьировать от едва заметных до угрожающих жизни гипотензии и дыхательной недостаточности. В крайней форме системный воспалительный ответ реализуется как фульминантный гемофагоцитарный лимфогистиоцитоз / синдром активации макрофагов (HLH / MAS), ассоциирующийся с очень высокой смертностью [39]. Существует очевидная взаимосвязь между объемом опухолевой массы и тя жестью СВЦ.…”
Section: применение Car T-клеток и биспецифических антител привлекающих т-клетки (Bispecific T-cell Engagers Biteunclassified